Mother or motherland: Can a government have an impact on educational attainment of the population? : preliminary evidence from India - Sumon Kumar Bhaumik; Manisha Chakrabarty (Institute for the Study of Labor (IZA), 2010)
In this paper, using data from the 61st round of the (Indian) National Sample Survey, we examine the relative impacts of personal-household and state-level characteristics (including government policy) on the likelihood of transition from one educational level to the next. Our analysis suggests that the most important factors driving these transition likelihoods are personal and household characteristics like gender and education of household heads. However, state-level characteristics and government policies have a significant impact on these transition likelihoods as well, especially for transitions from the lowest levels of education to somewhat higher levels. The odds of making the transition to higher education, especially tertiary education, are systematically lower for women than for men, for individuals in rural areas than those in urban areas, and for Muslims than for Hindus. An important conclusion of our analysis is that there is significant scope for government policy to address educational gaps between various demographic and other groups in the country.
Keywords: I21; I28; 330; Educational attainment; likelihood of transition; government policy; Bildungschancen; Bildungsverhalten; Bildungspolitik; Bildungsniveau; Indien